Agrarian Commonwealth or Entrepôt of the Orient? Competing Conceptions of Canada and the BC Terms of Union Debate of 1871 - Pass, Forrest (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2006)
AbstractMuch of the historiography of British Columbia’s 1871 entry into Confederation has concentrated on the motives of British Columbians in seeking union with Canada. This article examines the discussion of the province’s Terms of Union in the Canadian parliament and in the eastern Canadian press, and recasts the debate as a conflict between two competing visions of Canada’s economic future. Proponents of the admission of British Columbia believed access to the Pacific would transform the new Dominion into a commercial superpower. Opponents of the Terms looked upon distant, mountainous, and sparsely populated British Columbia as a liability, a region and a community that, unlike the Prairie West, could never conform to the agrarian ideal that underpinned their conception of Canada. A reconsideration of the Terms of Union debate in eastern Canada suggests a broader conception of what constitutes Canada’s founding debates, and supports the work of other scholars who have identified an agrarian-commercial cleavage as a defining feature of nineteenth-century Canadian politics.